2006
DOI: 10.3748/wjg.v12.i35.5687
|View full text |Cite
|
Sign up to set email alerts
|

Expressions of sonic hedgehog, patched, smoothened and Gli-1 in human intestinal stromal tumors and their correlation with prognosis

Abstract: These results suggest that the Hh signaling pathway may play an important role in myogenic differentiation and the malignant potential of human intestinal stromal tumors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
29
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(35 citation statements)
references
References 30 publications
5
29
0
1
Order By: Relevance
“…Recent years, the prognostic value of hedgehog components in some tumor types was reported (22)(23)(24)(25)(26). In the present study, we clearly show that many genes of hedgehog signaling upregulated in clinical ICC samples.…”
Section: Discussionsupporting
confidence: 69%
“…Recent years, the prognostic value of hedgehog components in some tumor types was reported (22)(23)(24)(25)(26). In the present study, we clearly show that many genes of hedgehog signaling upregulated in clinical ICC samples.…”
Section: Discussionsupporting
confidence: 69%
“…In other malignancies PTCH1 expression was correlated with high grade and advanced stage tumors suggesting that HH signaling may differentially affect tumor biology depending on the tissue context [9,41]. We also showed that SMO was overexpressed in NSCLC consistently with studies in other tumors [39,41,42]. Its expression differed among NSCLC types, being higher in squamous cell carcinomas similarly to PTCH1.…”
Section: Discussionsupporting
confidence: 68%
“…These data further implicate the Hh signaling pathway in prostate cancer progression. Reduced SHH is of interest because many clinical and scientific studies have reported that elevated SHH levels correlate with poor survival in patients or animals in various tumor types, including prostate cancer (17,(47)(48)(49)(50).…”
Section: Discussionmentioning
confidence: 99%